Fetal rhabdomyoma leads to family diagnosis of tuberous sclerosis complex - Yan-Dong Yang; Dong-Zhi Li (Journal of Medical Ultrasound, 2023)
Tuberous sclerosis complex (TSC) is a multisystem genetic disorder characterized by the growth of numerous noncancerous tumors in many parts of the body. It is highly variable in clinical presentations, including a wide range of cognitive, behavioral, and psychiatric manifestations. Of all the possible manifestations, cognitive and behavioral problems are the greatest concern to parents and physicians. In this study, two fetuses were identified to have rhabdomyomas by prenatal ultrasound. Carefully inquired familial medical history revealed other symptoms of TSC such as skin lesions or psychiatric problems in family members in the two families. Both fetuses and family members with positive clinical symptoms were confirmed to carry a familial TSC2 variant. Our study indicates that fetal echocardiography is not just the evaluation of the fetal heart. When fetal cardiac rhabdomyomas are diagnosed, a full family medical history and clinical assessment for TSC in family members should be undertaken.